Effects of Recycled Aggregate on Concrete Mix and Exposure to Chloride - Ammar Ben Nakhi; Jasem M. Alhumoud (Advances in Materials Science and Engineering)
Construction and demolition waste has dramatically increased in the last decade, and most of it goes into landfills, increasing the burden on landfill loading and operations. Recycling of concrete is needed from the viewpoints of environmental preservation and effective utilization of resources. Regarding the durability of concrete, chloride diffusion, which is one parameter that reflects the durability of concrete, is tested in this study. Concrete made with different percentages of recycled aggregate (0%–100%, with increments of 10%) is investigated using mechanical and nondestructive testing of mixes consisting of two aggregate particle sizes (1/2″ and 3/8″). In addition, we studied the chloride diffusion of saturated concrete made with different percentages of recycled aggregate. The samples were exposed to sea water with 3% chloride concentration and tested after 2 and 4 weeks of exposure. The results indicate that the density and air content of new concrete decreased with an increase in recycled aggregates content. Compressive strength decreased with the increase in the recycled aggregate content, and a concrete mix with 40% recycled aggregate exhibited the best strength. Concrete mix with 30% recycled aggregate had the lowest chloride penetration after 2 weeks of saturation and performed better than a concrete mix with 100% natural aggregate. Owing to the lower density and higher water absorption of recycled aggregates, chloride ion diffusion increased with increasing recycled aggregate content beyond 2 weeks.